(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: The present investigation was carried out to determine concentration of cadmium in milk and dairy products in Dak Lak in 2020. Objects and methods: A total of 150 samples of popular commercial milk and dairy products in the study area (based on data reported by the City Food Safety Bureau). In which, 10 powdered milk, 40 raw milk, 70 yogurt, 10 cheese and 20 milk cake samples were collected from farms, individual farmers and dairy shops in Dak Lak. It were analysed for determination their cadmium. Results: Cadmium was detectable in 107/150 samples. The mean concentrations of Cd in milk cake, cheese, raw milk, powdered milk and yogurt samples were 157,3 µg/L; 155,1 µg/L; 133,7 µg/L; 119,8 µg/L and 88,5 µg/L, respectively. On the other side, this study also reported that the contents of cadmium in all materials weren’t over the permissible levels of 1000 µg/L established by QCVN 8-2:2011/BYT. Conclusion: The use of these products is not affected by cadmium to consumers’ health.